Analyzing Students’ Decision-Making Style in Prior Knowledge of Mathematical Critical Thinking Skill - R N Hafni; E Nurlaelah (Pancaran Pendidikan, 2018)
Critical thinking is a higher-order thinking skill which is believed to be able to enhance students’ ability in facing academic as well as real life challenges and problems. Student’s thinking skill is affected by their prior knowledge and experience, which play an important part in the decision-making process, a crucial phase and a compound process taking a principal role in all thinking levels. The purpose of this research is to find out students’ critical thinking skill in order to recognize the characteristics of students' thinking based on decision-making style. This research is a case study adopting a qualitative approach, using descriptive analysis. The data are collected using test, observation and interview. The results show that more than half students’ critical thinking skill is still on the lower cognitive complexity based on the decision-making style.